A novel design of 3D carbon host for stable lithium metal anode. Issue 4 (29th April 2022) - Liu, Hang; Di, Jie; Wang, Ping; Gao, Rui; Tian, Han; Ren, Pengfei; Yuan, Qingxi; Huang, Wanxia; Liu, Ruiping; Liu, Qiang; Feng, Ming
Abstract: Rational design of porous conductive hosts with high electrical conductivity, large surface area, and adequate interior space is desirable to suppressing dendritic lithium growth and accommodating large volume change of lithium metal anode during the Li plating/stripping process. However, due to the conductive nature of the conductive hosts, Li is easily deposited directly on the top of the hosts, which hinders it from fully functioning. To circumvent the issue, in this study, we designed a novel porous carbon host with a gradient‐pore‐size structure based on one‐dimensional (1D) carbon with different diameters. With this kind of host, stable cycling with high and stable Coulombic efficiency of ~98% is achieved at 0.5 mA cm −2 with an areal capacity of 1 mAh cm −2 over 320 cycles. In contrast, the normal three‐dimensional (3D) carbon nanotube host presents a moss‐like Li morphology with wildly fluctuating Coulombic efficiency after 100 cycles. The results reveal that the unique gradient‐pore‐size structure of the 3D conductive host greatly improves the performance of lithium metal batteries. Abstract : A novel three‐dimensional carbon host with a gradient pore size distribution structure can efficiently guide Li growth, accommodate the deposited Li metal, and alleviate the severe volume changes during the Li plating/stripping process. Moreover, the unique gradient pore size distribution structure tackled the tricky problem of Li directly depositing on the top of the conductive host, making sure that the porous interior space is fully functional.